Pengaruh budaya organisasi dan lingkungan kerja terhadap kinerja tenaga kependidikan di Universitas Islam Bandung - Idris, Idris; Santoso, Anton Budi (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2023)
The main purpose of this research is to verify the influence of organizational culture and work environment on the performance of educational staff at Unisba either individually (partially) or jointly (simultaneously). This study used a quantitative method with data collection techniques using the questionnaire with total sample of 166 people. The data collected was tested and analyzed using several testing techniques, like validity test, reliability test and classical assumption test and multiple linear regression test. The test results show that the significance value of the organizational culture variable is 0.00, and ≤ 0.05, which means that partially organizational culture has a positive influence on the performance of education staff at Unisba. The results of the T test on work environment variables show a significance value of 0.00, and ≤ 0.05, which means that the work environment has a positive influence on the performance of education staff at Unisba. The results of the F test show a significance value of 0.00, and ≤ 0.05, which means that organizational culture and work environment with simultaneously have positive influence on the performance of education staff at Unisba. The results of multiple linear regression tests show the coefficient of determination (R2) is 0.584, that means organizational culture and work environment simultaneously influence the performance of educational staff about 58.4%, and 41.6% can be influenced by other factors or variables that are not taken in this research model.